Collaborative Integration of Indigenous Knowledge and Pedagogical Approaches in Science Education: A Systematic Review of Epistemological Perspectives (2020–2025) - Lintang Auliya Kurdiati (Abjadia : International Journal of Education, 2026)
Equipping learners to address contemporary environmental, technological, and societal challenges is a central objective of science education. However, curricula frequently prioritize Western scientific paradigms, resulting in the marginalization of indigenous knowledge systems that offer culturally meaningful and locally grounded insights. This systematic review synthesizes 11 empirical studies published between 2020 and 2025 that investigate the collaborative integration of indigenous knowledge and pedagogical approaches in science education, focusing on epistemological perspectives and educational implications. A comprehensive search was conducted across major academic databases, and relevant studies were screened using explicit inclusion and exclusion criteria to ensure rigor. The final corpus was analyzed to identify research characteristics, models of collaboration, epistemological lenses, and practical mechanisms. Findings indicate that collaborative integration strategies, including co-designed STEAM/STEM curricula and culturally responsive pedagogical approaches, enhance learner engagement, promote epistemic pluralism, and support contextually grounded learning experiences. Epistemological frameworks such as contextual constructivism, relational knowledge, and ethnoscience underpin effective integration, guiding curriculum design and instructional practice. The review concludes that embedding indigenous knowledge collaboratively with pedagogical strategies is critical for culturally responsive science education and offers actionable insights for educators, curriculum developers, and policymakers seeking pluralistic, context-sensitive, and ethically informed learning environments.